2007
DOI: 10.1243/09544119jeim202
|View full text |Cite
|
Sign up to set email alerts
|

The fate of implanted autologous chondrocytes in regenerated articular cartilage

Abstract: Autologous chondrocyte implantation (ACI) is used to treat some articular cartilage defects. However, the fate of the cultured chondrocytes after in-vivo transplantation and their role in cartilage regeneration remains unclear. To monitor the survival and fate of such cells in vivo, the chondrocytes were labelled with a lipophilic dye and the resultant regenerated tissue in dogs examined. It was found that, 4 weeks after implantation, the osteochondral defects were filled with regenerative tissue that resemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The transplanted chondrocytes can remain viable for a long time. [23][24][25][26] They can be traced using radioisotope cell labelling or fluorescence cell labelling and visualised using fluorescent or confocal microscopy or polymerase chain reaction. A mean of 87% of cell viability is maintained for up to 4 weeks; only 14% of the one million chondrocytes transplanted remained, but the total numbers of cells increase with time.…”
Section: Articular Cartilage Consists Of An Extracellular Matrix (Maimentioning
confidence: 99%
See 2 more Smart Citations
“…The transplanted chondrocytes can remain viable for a long time. [23][24][25][26] They can be traced using radioisotope cell labelling or fluorescence cell labelling and visualised using fluorescent or confocal microscopy or polymerase chain reaction. A mean of 87% of cell viability is maintained for up to 4 weeks; only 14% of the one million chondrocytes transplanted remained, but the total numbers of cells increase with time.…”
Section: Articular Cartilage Consists Of An Extracellular Matrix (Maimentioning
confidence: 99%
“…This suggests that ACT keeps the transplanted chondrocytes viable and promotes cell migration from the surrounding tissues. [23][24][25] Nonetheless, the source and fate of these cells were not determined. They may migrate into the surrounding tissues, participate in cell-mediated immune death or even in apoptosis.…”
Section: Articular Cartilage Consists Of An Extracellular Matrix (Maimentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable efforts have been made to develop suitable cartilage repair procedures resulting in defect filling and restoration of the articular surface with the best possible tissue repair. There is evidence to support the idea that application of ex vivo expanded chondrocytes or mesenchymal stromal cells (MSCs) are relevant for cell-based therapies [ 2 , 3 ]. However, use of chondrocytes has several drawbacks such as a two-stage surgical procedure that may cause further cartilage damage and degeneration and chondrocyte dedifferentiation during in vitro culture.…”
Section: Introductionmentioning
confidence: 99%
“…Based on available literature, it appears that the repair process following implantation of autologous chondrocytes may be the result of multiple biological and mechanistic cellular functions acting in concert (27). It has been suggested that among those most commonly described, the repopulation of implanted chondrocytes within the defect sites appears to be the more accepted notion (28).…”
Section: Discussionmentioning
confidence: 99%